IMPLEMENTASI KEBIJAKAN PEMERINTAH KOTA SEMARANG DALAM MENGATASI BANJIR DAN ROB TAHUN 2013 - Risiandi .; Yuwanto .; Wiwik Widayati (Journal of Politic and Government Studies, 2014)
From time to time Semarang experienced flooding and sea water overflowing. This is because in the north which also called Kota Bawah is located lower than the sea. Implementation Policy of government has tried various policies in addressing the flood and sea water overflowing through the polder system, elevating the road and installing drainage. But when it viewed from the conditions in the field that flooding and overflowing of sea water are increasingly venturing into the city, it can be said until now the problem cannot be resolved.The purpose of this study was to determine the efforts of Semarang City Government in the implementation policies and know the obstacles faced in addressing flood sea water overflowing. This research was conducted at the Department of Water Resources and Energy and Mineral Resources of Semarang. This study uses qualitative and descriptive type of analysis, while the method of data collection was conducted through interviews and observation.Based on the analysis of implementation policy by Donald S. Van meter and Carl E. Van Horn who has six indicators, namely; standards and objectives, resources, inter-organizational relationships, implementing characteristics, socio-economic and political conditions, implementers disposition yet also shows the effective and efficient results. The results of this study indicate that implementation policy of Semarang in addressing the flood and sea water overflow according to the Regional Regulation No. 14 Year 2011 about Spatial Planning of Semarang Year 2011-2031 not optimal due to the flood still happened in some parts of the city of Semarang like in Johar Market area of Semarang is always experienced flooding when the rainy season and suffered sea water overflows when the rising tide inundation that occurred in most of the area.Referring to the results of the study suggested implementation policy of Semarang Government to control the flood and sea water overflow in an integrated and sustainable thus produce a more optimal achievement.Efforts should be made by the Government such as constructing of the addition of water pumps, constructing of the addition of retention ponds and enhance cooperation with Japan International Corporate Agencies relevant parties to resolve the flood in the city of Semarang.Keywords: Implementation Policy; Floods; Sea water overflow